Down-Regulation of Phosphoribosyl Pyrophosphate Synthetase 1 Inhibits Neuroblastoma Cell Proliferation - Jifu Li; Junhong Ye; Shunqin Zhu; Hongjuan Cui (Cells, 2019)
Phosphoribosyl pyrophosphate synthetase 1 (PRPS1) is a key enzyme in de novo nucleotide synthesis and nucleotide salvage synthesis pathways that are critical for purine and pyrimidine biosynthesis. Abnormally high expression of PRPS1 can cause many diseases, including hearing loss, hypotonia, and ataxia, in addition to being associated with neuroblastoma. However, the role of PRPS1 in neuroblastoma is still unclear. In this study, we found that PRPS1 was commonly expressed in neuroblastoma cells and was closely related to poor prognosis for cancer. Furthermore, down-regulation of PRPS1 inhibited neuroblastoma cell proliferation and tumor growth in vitro and in vivo via disturbing DNA synthesis. This study provides new insights into the treatment of neuroblastoma patients and new targets for drug development.